Optimizing Teacher Recruitment and Compensation: Enhancing HR Practices in Basic Schools - Emmanuel Nii Tackie Tackey, Emmanuel; Tatsi, Samuel; Akafia, Charles; Kpakpo Allotey , Benjamin; Afful , Kingsley (MultiTech Publisher, 2024)
This study examined the recruitment, selection, and compensation processes at Basic School A, identifying areas for improvement in human resource management. Using a qualitative approach, semi-structured interviews were conducted with the headteacher and a purposive sample of teachers. Thematic analysis revealed that the recruitment process involves completing education, national service, applying through the GES portal, and documentation before posting. Teachers preferred the previous decentralized system for greater commitment and reduced transportation costs. The compensation process includes validation by the Accountant Generals’ Department to eliminate absenteeism and “ghost” employees, though some teachers are only aware of monthly credits. Both teachers and the headteacher highlight staffing as needing improvement, suggesting that decentralizing recruitment to consider teachers’ residences would enhance job satisfaction and performance. Recommendations include decentralizing recruitment to allow district selection, establishing transparent validation guidelines, and shifting towards decentralized staffing for better resource management and improved teacher commitment.